Angry girls will get us through - Traister, Rebecca; Shamir, Ruby (Simon & Schuster Books for Young Readers, 2026)
"Two starred reviews! In her "brilliant" (Kirkus Reviews, starred review) first book for young readers, New York Times bestselling author and New York magazine writer-at-large Rebecca Traister draws material from her award-winning books and articles to show girls their anger has the power to be a force of change, just like for many trailblazers before them. From an early age, young girls are taught anger isn't an emotion they should express. They're told-either implicitly or explicitly-to spend their lives keeping their fury locked inside for the benefit of others. But partly, Traister argues, that's because the anger of women and girls has been a crucial catalyst for change, putting in motion some of the most defining social and political movements in our nation's history. And it's that anger that will blaze the path forward for the future. Traister chronicles a concise history from the colonial era to the Women's March of 2016 demonstrating how women's rage has forged coalitions and created political change through movements for women's and civil rights and more, and how the past decade has created an inflection point for women and girls who have yet to experience rights equal to men's in the United States"-- Provided by publisher.